An occupational perspective on three solutions to unemployment. Issue 3 (3rd July 2018) - O'Halloran, David; Farnworth, Louise; Innes, Ev; Thomacos, Nikos
ABSTRACT: Unemployment is a key political and social issue with the number of unemployed predicted to grow into the future. Unemployment is also an occupational issue but one that has attracted relatively little attention in the occupational science literature. Being unemployed is the absence of a socially described type of occupation, i.e. work, which creates the potential for significant disruption to occupational balance and the opportunity for achieving health through occupation. Three solutions are considered using a framework based on the work of Wilcock and Hocking. The first solution is the current approach to dealing with unemployment, which presents a risk to the occupational well-being of individuals if employment is not found. Two alternative solutions - a Job Guarantee (JG) and a Universal Basic Income (UBI) offer some additional opportunities for health through occupation, with the UBI perhaps offering the greatest opportunity for occupation to create health. Using the framework has highlighted some gaps in the occupational science discussion. However, the unique insights offered by occupational science will count for little if occupational scientists do not contribute to the broader discourse, which requires familiarity with key economic and political issues.